Gerakan Gisel “Gizi Seimbang, Tumbuh Kembang Maksimal” Sebagai Upaya Menekan Angka Stunting - Saputri, Rizka; Ramdani, Mochamad; Yulia, Mita Ana; Ivana, Luthfi Amalia; Fahrizal, Erick; Sahidin, Diky Putra; Aceh, Bariatun Nufus; Jasmine, Aura Nadhiya; Aulia, Andhara Putri; Nurlaeli, Andini Siti; Muttaqin, Radhea Izzul (Yayasan Cendekia Gagayunan Indonesia, 2024)
Stunting is still a serious health problem in Indonesia. Based on data from the Ministry of Health, the stunting rate in Indonesia in 2023 is still at 21.5%. The government has taken various measures to reduce the stunting rate. The target is that by 2024, the stunting rate in Indonesia will drop to 14%. In order to help realize this, KKN students went directly to the field, precisely in Nangewer Village, Kersamenak Village, Tarogong Kidul District, Garut Regency to socialize stunting. Based on data from the local health center, in Kersamenak Village itself, there were 89 children who had been identified as stunting and one of the contributing factors was the lack of knowledge of the community, especially prospective parents, regarding stunting and nutrition. This activity uses the Service learning method by presenting material using standing X-Banners and virtual posters that are distributed on social media groups. Participants in this socialization were 10 PKK cadre mothers. The efforts made were to present the material using standing X-Banner and virtual posters starting from the definition of stunting, causes, physical and psychological impacts, and how to prevent it by implementing the